우리나라 제 2형 당뇨병 환자들의 임상적 특징 및 직접 의료비용 조사 - 조영은 (The Graduate School, Ajou University, 2007)
Purpose : The number of type 2 diabetic patients is exploded due to the continuously increasing length of the life span of individuals in combination with the growing number of the world population. Another important factor is the currently ongoing change in life style towards a more western-oriented way of living. The aim of this study was to analyze the direct medical costs attributable to type 2 diabetes and its determinants in Korea. Methods : We studied a random sample of patients with type 2 diabetes who have attended Ajou University Hospital in 2005. Demographic characteristics, duration of diabetes, glycemic control, complications were assessed by medical chart review and annual direct medical costs by computerized data. Results : Among 899 diabetic patients, 59.8% had at least one microvascular complication and 18.9% at least one macrovascular complication. 12.9% of patients had both microvascular and macrovascular complications. 26% had retinopathy, 35.5% neuropathy, 32.1% nephropathy, 12.9% cardiovascular complications, and 6.8% cerebrovascular complications. The average annual direct medical cost was found to be \3,086,663 per patient. In patients with both microvascular and macrovascular complications, the total cost of management was increased by 210% compared to those without complications. Conclusion : Complications have a substantial impact on the direct medical costs of type 2 diabetes. The prevention of diabetic complication by strict glucose and blood pressure control will not only influence mortality and morbidity of diabetic patients but potentially reduce medical cost.
학위논문(석사)--아주대학교 일반대학원 :의학과,2007.2
Keywords: 제 2형 당뇨병; 미세혈관 합병증; 대혈관 합병증; 직접 의료비용